How Staphylococcus epidermidis and Staphylococcus aureus cope with oxidative and nitrosative stress - Freitas, CS (2018)
"Staphylococcus epidermidis and Staphylococcus aureus are predominant colonizers of the human skin and important nosocomial pathogens. These pathogens form biofilms, mainly on implanted medical devices, that are resistant to antibiotics and to the chemicals produced by the host immune system. In particular, professional phagocytes of the innate immunity release toxic reactive oxygen species (ROS) and reactive nitrogen species (RNS) that are highly damaging to pathogens, whose survival depends on their defense mechanisms.(...)"